Etika Profesional HR dan Dampaknya terhadap Employer Branding serta Candidate Experience: Studi Kasus pada PT Zhao Hui Nickel (ZHN) Indonesia - Saniah Lidiya Hawani; Cris Diana Sidabutar; Joanna Brigitta; Heva Gracia Manurung; Nasrullah Hidayat (Publikasi Inspirasi Indonesia, 2026)
This study analyzes the violation of professional HR ethics within the recruitment process at PT ZHN Indonesia and its impact on Candidate Experience and Employer Branding. The issue emerged when an HR staff member verbally abused a candidate, the incident subsequently went viral and triggered a severe reputational crisis. This research aims to understand the causal relationship between unethical HR behavior, negative candidate experiences, and organizational image degradation. A qualitative case-study approach was employed, utilizing secondary data from news reports, social media reactions, official company statements, and relevant academic literature. The findings indicate that ethical violations induced a